Virtual proximity and audiovisual services trade - Martin Schmitz; Christiane Hellmanzik (European Central Bank (ECB), 2015)
Audiovisual services such as music and movies in digital formats have gained substantial importance over the last decade. This paper analyses audiovisual services in a gravity model framework. In particular, we explore the role of virtual proximity - a new proxy for cultural proximity based on bilateral hyperlinks and bilateral website visits between countries - and find that `virtually-proximate' countries trade significantly larger amounts of audiovisual services. Our results show that virtual proximity also has a larger impact on trade in audiovisual services than on total services trade. Moreover, in line with Hanson and Xiang (2011), our analysis indicates that in the audiovisual services sector, global fixed export costs dominate bilateral fixed export costs for most countries in our sample.
Keywords: F12; F15; Z10; 330; audiovisual services; cultural proximity; hyperlinks; International trade; internet